Polymer electrolyte, preparation method and application
By designing the co-continuous structure of polymer electrolytes in lithium-ion batteries, and using the combination of polymer elastomers and multivariate deep eutectic electrolytes, the problems of flammability and poor cycle stability in traditional batteries are solved, significantly improving the battery's magnification and low-temperature performance, and improving safety and energy density.
Patent Information
- Application Number
- CN202510090018.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-02-25
AI Technical Summary
The carbonate electrolytes in traditional lithium-ion batteries are flammable and have poor cycle stability, making it difficult to inhibit the growth of lithium dendrites in high-energy density lithium batteries, resulting in battery short circuits and safety accidents.
A polymer electrolyte is designed, which is formed by the polymerization-induced phase separation between the polymer elastomer and the multivariate deep eutectic electrolyte. Through the combination of the polymer elastomer as a mechanical framework and the multivariate deep eutectic electrolyte, the conduction speed of lithium ions, the magnification and low-temperature performance of the battery are improved.
It significantly improves the rate performance and low temperature performance of the battery, reduces the transmission energy barrier of lithium ions, and improves the safety and reliability of the battery.
Smart Images

Figure CN119518085A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrolyte and polymer lithium battery, and in particular to a polymer electrolyte, a preparation method and application thereof. Background Art
[0002] With the rapid development of application needs, people have higher requirements for driving range and driving capacity, and are paying more and more attention to high-energy-density electrode materials and high-safety electrolytes. Lithium metal and silicon-based anodes, due to their high theoretical specific capacity, can effectively improve battery energy density when matched with high-voltage cathodes such as nickel-cobalt-manganese ternary, lithium iron manganese phosphate, and lithium cobalt oxide.
[0003] However, the carbonate electrolytes used in traditional lithium-ion batteries have problems such as flammability and poor cycle stability. When carbonate solvent electrolytes are applied to the next generation of high-energy-density lithium batteries, it is difficult to inhibit the growth of lithium dendrites, which can easily cause battery short circuits and trigger safety accidents such as explosions.
[0004] Polymer deep eutectic electrolytes combine the advantages of deep eutectic electrolytes (fast ion transport, non-flammable properties) and solid electrolytes (strong mechanical properties) and have become a promising alternative to traditional polymer electrolytes.
[0005] For example, the Chinese patent with publication number CN116190777A discloses a cellulose-based eutectic gel electrolyte, which has a simple preparation method and has a high lithium salt solubility capacity, which improves the transmission of ions in the electrolyte. However, the current rate performance and low temperature performance of polymer electrolytes need to be further improved, mainly due to slow kinetics and unstable interfaces at low temperatures, which seriously hinder the application of batteries in cold environments. In order to improve the rate performance and low temperature performance of polymer electrolytes in solid-state battery applications.
[0006] The present invention designs a polymer electrolyte, which is a co-continuous structure formed by polymerization-induced phase separation between a polymer elastomer and a multinary deep eutectic electrolyte, and the polymer electrolyte includes a polymer elastomer and a multinary deep eutectic electrolyte. Among them, the polymer elastomer acts as a mechanical skeleton and can improve the film-forming property of the electrolyte. Multinary deep eutectic electrolytes have the advantages of intrinsic intrinsic safety, good ion conduction characteristics, and efficient ion conduction behavior at the interface. It is worth noting that the design of the strong polar functional groups on the polymer elastomer chain segments can anchor a large number of multinary deep eutectic electrolytes, and lithium ions have a faster conduction speed in this structure. At the same time, the design of the multinary deep eutectic electrolyte solvent improves the entropy change of the overall system, and the Gibbs free energy of the system is reduced accordingly. The ions have a lower ion transport energy barrier at room temperature or even low temperature, and the rate performance and low temperature performance of the battery are significantly improved. Summary of the invention
[0007] In view of this, the present invention provides a polymer electrolyte, using a multi-component deep eutectic electrolyte as the main carrier for lithium ion transmission and a polymer elastomer as a polymer skeleton. The polymer elastomer and the multi-component deep eutectic electrolyte in the prepared polymer electrolyte interact with each other, promoting the rapid conduction of lithium ions. In addition, the design of the multi-component deep eutectic electrolyte as an ion-conducting phase improves the entropy change of the overall system, and the Gibbs free energy of the system is reduced accordingly. Lithium ions have a lower transmission energy barrier at room temperature or even low temperature, and the battery rate and low-temperature performance are significantly improved accordingly.
[0008] The first aspect of the present invention provides a polymer electrolyte, wherein the polymer electrolyte is a co-continuous structure formed by polymerization-induced phase separation between a polymer elastomer and a multi-element deep eutectic electrolyte; and comprises the following components by mass fraction: The mass of polymer elastomer accounts for 5~50%; The mass of multi-element deep eutectic electrolyte accounts for 50~95%.
[0009] A second aspect of the present invention provides a method for preparing a polymer electrolyte, comprising the following steps: S1. Mixing a lithium salt, a hydrogen bond donor and an additive containing an O=S=O group, stirring at 25-100° C. for 0.5-24 hours, to obtain a multi-element deep eutectic electrolyte; S2, mixing the amide vinyl monomer and the initiator to obtain a polymer elastomer; S3. Mix and stir the multi-element deep eutectic electrolyte obtained in step S1 and the polymer elastomer obtained in step S2, inject them into the battery for infiltration for 2h to 48h, polymerize them at a temperature range of 25 to 120°C for 0.5h to 48h to obtain the polymer electrolyte, which is present in the battery.
[0010] Preferably, the molar ratio of the lithium salt, the hydrogen bond donor and the additive containing the O=S=O group in step S1 is (5-20):(60-90):(2-20).
[0011] Preferably, the mass ratio of the amide vinyl monomer to the initiator in step S2 is (90 ~ 99.5): (0.1 ~ 5).
[0012] Preferably, the lithium salt in step S1 is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium perchlorate.
[0013] Preferably, the hydrogen bond donor in step S1 is one or more of succinonitrile, N-methylacetamide, urea and 1,3-dimethyl-2-imidazolidinone.
[0014] As the main action site of lithium salt, hydrogen bond donor can reduce the melting point of the whole system through the eutectic effect with hydrogen bond acceptors such as lithium salt, thus constructing a deep eutectic electrolyte. + ] solvation structure for ion transport. Among them, the deep eutectic electrolyte prepared by nitrile hydrogen bond donors represented by succinonitrile, amide hydrogen bond donors represented by N-methylacetamide, urea hydrogen bond donors represented by urea, and imidazole hydrogen bond donors represented by 1,3-dimethyl-2-imidazolidinone and lithium salt eutectic has excellent ionic conductivity and thermal stability.
[0015] Preferably, the additive containing the O=S=O group in step S1 includes: one or more of sulfolane, dimethyl sulfoxide, vinyl sulfate, 1-propylene-1,3-sultone, propane sultone, methylene disulfonate, 4-vinyl vinyl sulfite, vinyl sulfite, and sulfite esters.
[0016] Additives containing O=S=O groups have lower lowest unoccupied molecular orbital (LUMO) energy levels, so sulfur-containing additives are generally more prone to electrochemical reduction, which is an ideal feature for good SEI formation. Second, the electronegativity of sulfur is comparable to that of carbon, which makes organic sulfur chemistry almost as rich as classical carbon chemistry - a favorable feature for tailoring the performance of electrolyte additives to application scenarios. Third, sulfur reserves are abundant and easily accessible, which ensures low-cost large-scale production of sulfur-containing compounds, an important parameter that the battery industry must consider.
[0017] Preferably, the amide vinyl monomer in step S2 is one or more of N,N-dimethylacrylamide, N,N-methylenebisacrylamide, acrylamide and derivatives thereof.
[0018] The selection of polymer monomers is crucial. Polymer monomers can anchor more eutectic electrolyte molecules through differences in electronegativity, thereby improving the ionic conductivity of the electrolyte. The carbonyl oxygen atom in the amide-based polymer monomer has a strong electron-withdrawing ability and can interact strongly with the α-H atom in succinonitrile, the amide functional group in N-methylacetamide, the urea group in urea, and the imidazole group in 1,3-dimethyl-2-imidazolidinone. A small number of polymer monomers can anchor a large amount of eutectic electrolyte. It is worth noting that the use of a variety of hydrogen bond donors can increase the entropy change of the electrolyte. According to the laws of thermodynamics, the Gibbs free energy of the electrolyte decreases accordingly, and the energy barrier for ion migration is greatly reduced, thereby increasing the fast charging speed of the battery and the high and low temperature performance of the battery.
[0019] Preferably, the initiator in step S2 is one or more of azobisisobutyronitrile, dibenzoyl peroxide, dimethyl azobisisobutyrate and derivatives thereof.
[0020] A third aspect of the present invention provides an application of a polymer electrolyte in a solid-state battery. The solid-state battery comprises an electrolyte, a positive electrode, a negative electrode, and a separator. The electrolyte is prepared by an in-situ curing method.
[0021] In-situ solidification is a method for preparing a solid electrolyte by injecting a liquid electrolyte into the battery. After the electrolyte fully infiltrates the electrodes and the separator, a polymerization reaction is initiated in the electrolyte system under heating stimulation, and the electrolyte is converted into a solid electrolyte. This electrolyte preparation method improves the contact between the electrode and the electrolyte and reduces the interface impedance between the electrode and the electrolyte.
[0022] Preferably, the positive electrode active material can be selected from one or more of lithium iron phosphate and high-voltage positive electrode ternary nickel cobalt manganese oxide, lithium cobalt oxide, nickel cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt aluminum oxide, nickel cobalt manganese aluminum oxide, lithium iron manganese phosphate, lithium iron phosphate, sulfur, and lithium sulfide; the negative electrode material is metallic lithium, graphite, silicon negative electrode, silicon carbon negative electrode, silicon oxide and lithium titanate; the diaphragm is one or more of commercial PP, PE, PI, cellulose film, PET porous film and ceramic coating film.
[0023] In order to improve the energy density of the battery, it is crucial to increase the battery voltage and the capacity of the single cell. The matching of high theoretical specific capacity lithium metal anode and silicon-based anode with high voltage nickel cobalt manganese, lithium cobalt oxide, and lithium iron manganese phosphate can greatly improve the battery energy density.
[0024] Beneficial effects of the present invention: (1) Multi-element deep eutectic electrolyte solvents increase the entropy change of the overall system, which reduces the Gibbs free energy of the system. Ions have a lower ion transport barrier at room temperature or even low temperature, which greatly improves the battery's rate and low-temperature performance. (2) A strong interaction is formed between the polymer elastomer skeleton and the multi-element deep eutectic electrolyte, which enables more multi-element eutectic electrolytes to be anchored in the skeleton, increasing the percentage of highly conductive deep eutectic electrolytes. The ionic conductivity of the polymer electrolyte has exceeded 10 -3 S cm -1 , the electrochemical window reaches ~5V, matching the high-voltage cathode material, and the energy density is greatly improved; (3) The intrinsic safety of eutectic electrolyte improves the safety and reliability of the entire battery system. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the implementation mode will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a morphological diagram of the phase separation structure between polymer elastomer and multi-element deep eutectic electrolyte at the 200 nanometer scale.
[0027] Figure 2 This is a test result diagram of the polymer electrolyte prepared in Example 1 being ignited for 10 seconds.
[0028] Figure 3 This is a graph showing the electrochemical window test results for the polymer electrolyte prepared in Example 1.
[0029] Figure 4 This is a graph showing the charge and discharge cycle test results of Li|lithium iron phosphate assembled with the polymer electrolyte prepared in Example 1 at -40°C.
[0030] Figure 5 This is a graph showing the charge and discharge cycle test results of Li|lithium iron phosphate assembled with the polymer electrolyte prepared in Example 1 at 80°C.
[0031] Figure 6 This is a graph showing the rate charge and discharge cycle test results of Li|lithium iron phosphate assembled with the polymer electrolyte prepared in Example 1.
[0032] Figure 7 This is a graph showing the charge and discharge cycle test results of Li|NiCoMn assembled with the polymer electrolyte prepared in Example 2 at -40°C.
[0033] Figure 8 This is a graph showing the charge and discharge cycle test results of Li|NiCoMn assembled with the polymer electrolyte prepared in Example 2 at 80°C.
[0034] Fig. 9 This is a graph showing the rate charge-discharge cycle test results of the Li|NiCoMn assembled with the polymer electrolyte prepared in Example 2. DETAILED DESCRIPTION
[0035] The following are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications may be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
[0036] Example 1 S1. In an argon glove box, 5.6 g of succinonitrile, 2.87 g of lithium bis(trifluoromethanesulfonyl imide), and 2.48 g of vinyl sulfate were weighed and mixed, and heated and stirred at 80° C. for 6 h to obtain a multi-element deep eutectic electrolyte; S2. In an argon glove box, 10 g of N,N-dimethylacrylamide and 0.05 g of azobisisobutyronitrile were weighed and mixed, and the mixture was stirred for 6 h to obtain a polymer elastomer; S3, weighing 1 g of polymer elastomer and 10 g of deep eutectic electrolyte in an argon glove box, respectively, mixing and stirring for 12 h to obtain a polymer multi-element deep eutectic electrolyte precursor; S4. In a glove box filled with argon, assemble a battery using lithium iron phosphate as the positive electrode, metallic lithium as the negative electrode and a commercial PP porous diaphragm, and then use the polymer multi-element deep eutectic electrolyte precursor prepared in step S3 as the electrolyte. After assembly, soak at room temperature for 24 hours and cure at 70°C for 4 hours to obtain an in-situ polymerized solid-state battery.
[0037] like Figure 1 As shown, the polymer electrolyte prepared in this embodiment presents a phase separation structure morphology of a polymer elastomer and a multi-element deep eutectic electrolyte phase at 200 nanometers, which promotes the rapid transmission of lithium ions.
[0038] like Figure 2 As shown, the polymer electrolyte prepared in this example is non-flammable, indicating that the polymer electrolyte has high safety.
[0039] like Figure 3 As shown, the electrochemical window of the polymer electrolyte prepared in this embodiment can reach 5.25V.
[0040] The electrolyte was used in a lithium battery with lithium metal as the negative electrode and lithium iron phosphate as the positive electrode and a full battery test was performed, such as Figure 4 As shown, the prepared solid-state battery was subjected to a 0.1C constant current charge and discharge test at -40°C, and there was no capacity decay after 10 cycles.
[0041] The electrolyte was used in a lithium battery with lithium metal as the negative electrode and lithium iron phosphate as the positive electrode and a full battery test was performed, such as Figure 5 As shown, the solid-state battery has no capacity decay after cycling for 100 weeks at 1C rate at 80°C.
[0042] The electrolyte was used in a lithium battery with lithium metal as the negative electrode and lithium iron phosphate as the positive electrode and a full battery test was performed, such as Figure 6 As shown, the solid-state battery can still be cycled at a 10C rate, indicating that the battery has good rate performance.
[0043] Example 2 S1. In an argon glove box, 5.6 g of succinonitrile, 2.87 g of lithium bis(trifluoromethanesulfonyl)imide, 0.94 g of methylene disulfonate, 0.62 g of vinyl sulfate, 0.6 g of 1-propylene-1,3-sultone, and 0.54 g of vinyl sulfite were weighed and mixed, and heated and stirred at 80° C. for 6 h to obtain a multi-element deep eutectic electrolyte; S2. In an argon glove box, 10 g of N,N-dimethylacrylamide and 0.05 g of azobisisobutyronitrile were weighed and mixed, and the mixture was stirred for 6 h to obtain a polymer elastomer; S3, weighing 1 g of polymer elastomer and 10 g of multi-component deep eutectic electrolyte in an argon glove box, respectively, mixing and stirring for 12 h to obtain a polymer multi-component deep eutectic electrolyte precursor; S4. In a glove box filled with argon, assemble a button cell using nickel-cobalt-manganese as the positive electrode, metallic lithium as the negative electrode and a commercial PP porous diaphragm, and then use the polymer electrolyte precursor prepared in step S3 as the electrolyte. After assembly, soak at room temperature for 4 hours and cure at 80°C for 18 hours to obtain an in-situ polymerized solid-state lithium battery.
[0044] The electrolyte was used in a lithium battery with lithium metal as the negative electrode and nickel-cobalt-manganese as the positive electrode and a full battery test was performed, such as Figure 7 As shown, the prepared solid-state battery was subjected to a 0.1C constant current charge and discharge test at -40°C, and there was no capacity decay after 10 cycles.
[0045] The electrolyte was used in a lithium battery with lithium metal as the negative electrode and nickel-cobalt-manganese as the positive electrode and a full battery test was performed, such as Figure 8 As shown, the solid-state battery has no capacity decay after cycling at 1C rate at 80°C for 60 weeks.
[0046] The electrolyte was used in a lithium battery with lithium metal as the negative electrode and nickel-cobalt-manganese as the positive electrode and a full battery test was performed, such as Fig. 9 As shown, the solid-state battery can still be cycled at a rate of 8C, indicating that the battery has good rate performance.
[0047] Example 3 S1. In an argon glove box, 5.6 g of succinonitrile, 2.87 g of lithium bis(trifluoromethanesulfonyl)imide, 0.94 g of methylene disulfonate, 0.62 g of vinyl sulfate, 0.6 g of 1-propylene-1,3-sultone, and 0.54 g of vinyl sulfite were weighed and mixed, and heated and stirred at 80° C. for 6 h to obtain a multi-element deep eutectic electrolyte; S2. In an argon glove box, 10 g of N,N-dimethylacrylamide and 0.05 g of azobisisobutyronitrile were weighed and mixed, and the mixture was stirred for 6 h to obtain a polymer elastomer; S3, weighing 1 g of polymer elastomer and 10 g of multi-component deep eutectic electrolyte in an argon glove box, respectively, mixing and stirring for 12 h to obtain a polymer multi-component deep eutectic electrolyte precursor; S4. In a glove box filled with argon, assemble a button cell using nickel-cobalt-manganese as the positive electrode, silicon-carbon as the negative electrode and a commercial PP porous diaphragm, and then use the polymer electrolyte precursor prepared in step S3 as the electrolyte. After assembly, soak at room temperature for 4 hours and cure at 80°C for 18 hours to obtain an in-situ polymerized solid-state lithium battery.
[0048] Example 4 S1. In an argon glove box, 5.6 g of succinonitrile, 2.87 g of lithium bis(trifluoromethanesulfonyl)imide, 0.94 g of methylene disulfonate, 0.62 g of vinyl sulfate, 0.6 g of 1-propylene-1,3-sultone, and 0.54 g of vinyl sulfite were weighed and mixed, and heated and stirred at 80° C. for 6 h to obtain a multi-element deep eutectic electrolyte; S2. In an argon glove box, 10 g of N,N-dimethylacrylamide and 0.05 g of azobisisobutyronitrile were weighed and mixed, and the mixture was stirred for 6 h to obtain a polymer elastomer; S3, weighing 1 g of polymer elastomer and 10 g of multi-component deep eutectic electrolyte in an argon glove box, respectively, mixing and stirring for 12 h to obtain a polymer multi-component deep eutectic electrolyte precursor; S4. In a glove box filled with argon, assemble a button cell using nickel-cobalt-manganese as the positive electrode, graphite as the negative electrode and a commercial PP porous diaphragm, and then use the polymer electrolyte precursor prepared in step S3 as the electrolyte. After assembly, soak at room temperature for 4 hours and cure at 80°C for 18 hours to obtain an in-situ polymerized solid-state lithium battery.
[0049] Example 5 The 5.6 g of succinonitrile in step S1 of Example 1 was replaced with 5.1 g of N-methylacetamide, and the other steps were the same as those of Example 1.
[0050] Example 6 The 5.6 g of succinonitrile in step S1 of Example 2 was replaced with 5.1 g of N-methylacetamide, and the other steps were consistent with Example 2.
[0051] Example 7 The 5.6 g of succinonitrile in step S1 of Example 1 was replaced with 4.2 g of urea, and the other steps remained unchanged.
[0052] Example 8 The 5.6 g of succinonitrile in step S1 of Example 2 was replaced with 4.2 g of urea, and the other steps were consistent with Example 2.
[0053] Example 9 The 5.6 g of succinonitrile in step S1 of Example 1 was replaced with 8 g of 1,3-dimethyl-2-imidazolidinone, and the other steps were consistent with Example 1.
[0054] Example 10 The 5.6 g of succinonitrile in step S1 of Example 3 was replaced with 8 g of 1,3-dimethyl-2-imidazolidinone, and the other steps were consistent with Example 3.
[0055] Comparative Example 1 S1. In an argon glove box, 5.6 g of succinonitrile and 2.87 g of lithium bis(trifluoromethanesulfonyl imide) were weighed and mixed, and heated and stirred at 80° C. for 6 h to obtain a deep eutectic electrolyte; S2. In an argon glove box, weigh 10 g of N,N-dimethylacrylamide and 0.05 g of azobisisobutyronitrile, mix them, and stir for 6 hours to obtain a polymer elastomer; S3, in an argon glove box, weighing 1 g of a polymer elastomer and 10 g of a deep eutectic electrolyte, respectively, mixing the mixture and stirring for 12 h to obtain a polymer deep eutectic electrolyte precursor; S4. In a glove box filled with argon, assemble a battery using lithium iron phosphate as the positive electrode, metallic lithium as the negative electrode and a commercial PP porous separator, and then use the polymer deep eutectic electrolyte precursor prepared in step S3 as the electrolyte. After assembly, soak at room temperature for 24 hours and cure at 70°C for 4 hours to obtain an in-situ polymerized solid-state battery.
[0056] The high and low temperature performance and rate performance of the batteries prepared in each embodiment and comparative example are shown in the table below.
[0057] Table 1 High and low temperature performance and rate performance of the batteries prepared in Examples 1-10 and Comparative Example 1
[0058] According to the above results, the multi-element deep eutectic electrolyte solvent increases the entropy change of the overall system, and the Gibbs free energy of the system decreases accordingly. The ions have a lower ion transport energy barrier at room temperature or even low temperature, and the battery rate and low-temperature performance are significantly improved accordingly.
[0059] The solid-state battery prepared by the preparation method provided by the present invention has a wide operable temperature range and excellent rate performance, and is expected to be equipped with HEV vehicles, and the obtained HEV vehicles are expected to be used on a large scale in areas with lower and higher temperatures.
Claims
1. A polymer electrolyte, characterized in that The polymer electrolyte is a co-continuous structure, which is formed by polymerization-induced phase separation between a polymer elastomer and a multi-element deep eutectic electrolyte; the polymer electrolyte includes the following components by mass fraction: The mass of polymer elastomer accounts for 5~50%; The mass of multi-element deep eutectic electrolyte accounts for 50~95%; The preparation method of the polymer electrolyte comprises the following steps: S1. Mixing a lithium salt, a hydrogen bond donor and an additive containing an O=S=O group, stirring at 25-100° C. for 0.5-24 hours, to obtain a multi-element deep eutectic electrolyte; S2, mixing the amide vinyl monomer and the initiator to obtain a polymer elastomer; S3. Mix and stir the multi-element deep eutectic electrolyte obtained in step S1 and the polymer elastomer obtained in step S2, inject them into the battery for infiltration for 2h to 48h, heat and polymerize them at a temperature range of 25 to 120°C for 0.5h to 48h to obtain the polymer electrolyte, which is present in the battery.
2. The method for preparing a polymer electrolyte according to claim 1, characterized in that: The molar ratio of the lithium salt, the hydrogen bond donor and the additive containing the O=S=O group in step S1 is (5-20):(60-90):(2-20).
3. The method for preparing a polymer electrolyte according to claim 1, characterized in that: The mass ratio of the amide vinyl monomer to the initiator in step S2 is (90 ~ 99.9): (0.1 ~ 10).
4. The method for preparing a polymer electrolyte according to claim 1, characterized in that: The lithium salt in step S1 is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate and lithium perchlorate.
5. The method for preparing a polymer electrolyte according to claim 1, characterized in that: The hydrogen bond donor in step S1 is one or more of succinonitrile, N-methylacetamide, urea and 1,3-dimethyl-2-imidazolidinone.
6. The method for preparing a polymer electrolyte according to claim 1, characterized in that: The additive containing the O=S=O group in step S1 is one or more of sulfolane, dimethyl sulfoxide, vinyl sulfate, 1-propylene-1,3-sultone, propane sultone, methylene methanedisulfonate, 4-vinyl vinyl sulfite, vinyl sulfite and sulfite ester.
7. The method for preparing a polymer electrolyte according to claim 1, characterized in that: The amide vinyl monomer in step S2 is one or more of N,N-dimethylacrylamide, N,N-methylenebisacrylamide, acrylamide and derivatives thereof.
8. The method for preparing a polymer electrolyte according to claim 1, characterized in that: The initiator in step S2 is one or more of azobisisobutyronitrile, dibenzoyl peroxide, dimethyl azobisisobutyrate and derivatives thereof.
9. Use of the polymer electrolyte prepared by the method for preparing the polymer electrolyte according to claims 1 to 8 in solid-state batteries.
Citation Information
Patent Citations
Cellulose-based eutectic gel electrolyte as well as preparation method and application thereof
CN116190777A
Monomer and polymer for gel electrolyte material, and preparation methods and applications of monomer and polymer
CN106374139A
Method for preparing all-solid-state battery through in-situ solidification
CN109994783A
Anti-zinc dendrite solid-state zinc-based battery electrolyte and preparation method thereof
CN114122534A
Polymer solid electrolyte with high lithium ion conductivity at room temperature
CN115775916A
Cited By
Recoverable Turing structure polymer electrolyte as well as preparation method and application thereof
CN121097199A
Preparation method and application of polymer electrolyte
CN121260911A